(untitled) - Takaki, Ronald T. (Boston, 1989)
In an extraordinary blend of narrative history, personal recollections, and oral testimony, Ronald Takaki presents a panoramic history of Asian Americans. He writes of the Chinese who laid tracks for the transcontinental railroads, of plantation laborers in the cane fields of Hawaii, of "picture brides" marrying strangers in hopes of becoming part of the American dream. The dark side of the dream is revealed too, in stories of Japanese internment camps, Hmong refugees tragically unable to adjust to Wisconsin's alien climate and culture, and Asian American students victimized today by a resurgence of racism. Takaki's moving and powerful work will resonate for all Americans-who together make up a nation of immigrants from different shores.
Keywords: Asian Americans,Asian Americans,Người Mỹ gốc Á,Người Mỹ gốc Á; History,Social conditions,Lịch sử,Điều kiện xã hội